2022
DOI: 10.1038/s41598-022-06866-5
|View full text |Cite
|
Sign up to set email alerts
|

Casimir forces out of thermal equilibrium near a superconducting transition

Abstract: We present a comprehensive analysis of the out-of-equilibrium Casimir pressure between two high-$$T_c$$ T c superconducting plates, each kept at a different temperature. Two interaction regimes can be distinguished. While the zero-point energy dominates in the near field, thermal effects become important at large interplate separations causing a drop in the force’s magnitude compared with the usual thermal-equilibriu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In each figure, the bottom, middle, and top lines are plotted for the graphene-plate temperature T g = 77 K, 300 K, and 500 K, respectively. In Figures 6(a from an ideal metal plane (32), whereas in Figures 6(b) and 7(b) -to the classical limit of the Casimir-Polder force F cl from an ideal metal plane (34).…”
Section: Nonequilibrium Casimir-polder Force From Fused Silica Plate ...mentioning
confidence: 99%
“…In each figure, the bottom, middle, and top lines are plotted for the graphene-plate temperature T g = 77 K, 300 K, and 500 K, respectively. In Figures 6(a from an ideal metal plane (32), whereas in Figures 6(b) and 7(b) -to the classical limit of the Casimir-Polder force F cl from an ideal metal plane (34).…”
Section: Nonequilibrium Casimir-polder Force From Fused Silica Plate ...mentioning
confidence: 99%
“…The theory of nonequilibrium Casimir and Casimir-Polder forces was further generalized to the case of nonplanar configurations [56][57][58][59][60] and for the plate materials with temperature-dependent dielectric permittivities [61][62][63][64][65]. It was also confirmed experimentally by measuring the nonequilibrium Casimir-Polder force between the Bose-Einstein condensate of 87 Rb atoms and a SiO 2 plate, which was heated as compared to the environmental temperature [66].…”
Section: Introductionmentioning
confidence: 85%
“…This suggests that the use of high-temperature superconductors (HTSCs), with T c ≈ 100 K, could constitute a suitable alternative to perform a direct analysis of the effect of the SC transition on the Casimir effect. In previous works, we investigated the Casimir forces between objects made of optimally doped YBa 2 Cu 3 O 7−δ (YBCO), with T c = 93 K , either in thermal [25], or out of thermal equilibrium [26]. In the first case, we found that the Casimir force displays an abrupt increment as the T → T c , for temperatures T > T c .…”
Section: Of 12mentioning
confidence: 98%